A 500 MS/s waveform digitizer for PandaX dark matter experiments. (21st December 2021) - He, C.; Liu, J.; Ren, X.; Shang, X.; Wei, X.; Wang, M.; Yang, J.; Yang, J.; Yang, Y.; Zhang, G.; Zheng, Q.
Abstract: Waveform digitizers are key readout instruments in particle physics experiments. In this paper, we present a waveform digitizer for the PandaX dark matter experiments. It supports both external-trigger readout and triggerless readout, accommodating the needs of low rate full-waveform readout and channel-independent low threshold acquisition, respectively. This digitizer is a 8-channel VME board with a sampling rate of 500 MS/s and 14-bit resolution for each channel. A digitizer system consisting of 72 channels has been tested in situ of the PandaX-4T experiment. We report the system performance with real data.